Perceived support, social and marital challenges in the lives of breast cancer survivors after illness: a self-administered cross-sectional survey - Ammar-Shehada, Walaa; Abusaman, Khaled; Bracke, Piet (Frontiers in Sociology, 2023)
Background Breast cancer (BC) is a traumatic illness. BC is the leading female cancer in Palestine. Complex socio-political dynamics impact patients’ lives, resulting in an increasing need for social support to develop resilience after illness. Methods Data was collected through a cross-sectional survey targeting women living in the Gaza Strip who had been diagnosed with BC. The survey was self-administered and distributed to 350 women between 1 March and 30 May 2021. Descriptive statistics and multinomial logistic regression analysis (SPSS, version 28.0) were used to explore perceived support, post-illness social and marital changes and the association between these changes and socio-demographic, illness-related and support-related variables. Findings About four-fifth of the women with BC felt supported after illness, either fully or partially, mainly by family members, non-governmental organisations, spouses, and peers. Nevertheless, nearly half of the women perceived negative social changes after illness, and about 40% of married or formerly married women perceived negative changes in their marital life. Survivors’ lived experiences varied by age, marital status, motherhood, prescribed treatment (specifically mastectomy), and the absence of informal support in social life and lack of partner support amongst married or formerly married women. Conclusion This study shows how BC undermines the social status of women and further exacerbates existing social vulnerabilities. Nevertheless, it is possible to manage and potentially overturn this circumstance by enveloping patients with social support. Guiding partners, families, and friends on providing emotional and instrumental support will help survivors to cope better during recovery.